Future of Food – Securing the Feeding of Asia: Policy Recalibration Needed - Teng, Paul (2017)
The challenge of having to increase food production by an estimated 50% by the year 2050 is becoming real. Government policies need to be recalibrated if this challenge of feeding many billions of mouths and addressing nutritional challenges are to be realised.